2015
DOI: 10.1021/acs.nanolett.5b01531
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-Roll Encapsulation of Metal Nanowires between Graphene and Plastic Substrate for High-Performance Flexible Transparent Electrodes

Abstract: Transparent conductive film on plastic substrate is a critical component in low-cost, flexible, and lightweight optoelectronics. Industrial-scale manufacturing of high-performance transparent conductive flexible plastic is needed to enable wide-ranging applications. Here, we demonstrate a continuous roll-to-roll (R2R) production of transparent conductive flexible plastic based on a metal nanowire network fully encapsulated between graphene monolayer and plastic substrate. Large-area graphene film grown on Cu f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
363
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(369 citation statements)
references
References 43 publications
4
363
0
2
Order By: Relevance
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…The growth of large‐area high‐quality graphene films is fundamental for the upcoming graphene applications. Chemical vapour deposition (CVD) method offers good prospects to produce large‐size graphene films due to its simplicity, controllability and cost‐efficiency 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75. Many researches have verified that graphene can be catalytically grown on metallic substrates, like ruthenium (Ru),13, 14 iridium (Ir),15, 16 platinum (Pt),17, 18, …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of applications of hybrid AgNW-graphene have been demonstrated in the literature ranging from its use as electrodes in light-emitting diodes to atomically thin barrier layer for protection against high-energy radiation [21,29,30,[52][53][54][55][56][57][58][59][60][61]. The schematic shown in Figure 6 summarizes the recent progress in the field and Table 2 presents their key physical properties.…”
Section: Multifunctional Applications Of Copercolating Hybrid Tcesmentioning
confidence: 99%
“…Recently, Deng et al [29] and Chandrashekhar et al [30] have reported RTR manufacturing of hybrid silver nanowiregraphene films with exceptionally good properties. These efforts have not only provided the prototype laboratory based multifunctional applications of hybrid copercolating TCE, but could also enable mass production of related components.…”
Section: Scalable Manufacturing and Possible Industrial Applicationsmentioning
confidence: 99%
See 2 more Smart Citations